IMPLEMENTASI PENGAWASAN DAN PENGELOLAAN ALOKASI DANA DESA OLEH PEMERINTAH DAN MASYARAKAT DI DESA ENGKERSIK - Alipius E.01108035 (FISIP Universitas Tanjungpura, 2013)
This article is intended to provide an understanding of how the implementation of the Managed Allocation Fund Oversight village where there is a lack of government oversight of the management of the Village Engkersik Village Allocation Fund. This study aims to determine the extent of the Government's role in overseeing the Village Village Allocation Fund and the role of community participation in the management of the Village in the Village Allocation Fund Engkersik. This research includes descriptive study with qualitative analysis, ie by giving an overview of the state or a painting of the subject and the object. Data collection techniques used observation, interview and documentation of the research subjects were adapted to the purpose of research. Instrument in this study is the researchers themselves who helped guide the interview and document recording devices. Based on existing data, the authors attempt to describe or depict in a systematic, factual and accurate information on the facts, properties and relationships between phenomena. These results indicate that the management of the Village Fund Allocation in the construction carried out in the Village District Sekadau Hilir Regency Engkersik Sekadau going pretty good, does not conflict with the planning documents and implementation procedures. Socialization and planning stages have been carried out by well without significant barriers, until completion of the Village Fund Allocation planning. However, if it is linked to the achievement of objectives, the implementation of Village Allocation Fund in the village Engekrsik not optimal. Due to the lack of adherence level, supervision and participation of the community. Advice from researchers to village government, Village Consultative Body, and Society Rural Engkersik improve oversight of the management of the Village Fund Allocation. Furthermore Village Government gives confidence to the public to participate in the management of the Village Fund Allocation. Because society that knows what became of their desires and feel the results of such development.Keywords: Implementation Oversight, Budget Management, Policy Compliance , Community Participation